2022
DOI: 10.1038/s41598-022-17327-4
|View full text |Cite
|
Sign up to set email alerts
|

Metformin treatment is associated with improved outcome in patients with diabetes and advanced heart failure (HFrEF)

Abstract: The role of metformin (MET) in the treatment of patients with advanced HFrEF and type 2 diabetes mellitus (DM) is not firmly established. We studied the impact of MET on metabolic profile, quality of life (QoL) and survival in these patients. A total of 847 stable patients with advanced HFrEF (57.4 ± 11.3 years, 67.7% NYHA III/IV, LVEF 23.6 ± 5.8%) underwent clinical and laboratory evaluation and were prospectively followed for a median of 1126 (IQRs 410; 1781) days for occurrence of death, urgent heart transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…There was a trend of additional bene t in patients with LVEF ≤40%, but the difference was not statistically signi cant. This result is in line with another recent study, which showed that metformin was associated with improved outcomes in patients with HFrEF and diabetes [31]. Although the study population was small, this study also found that metformin-treated patients with HF had better glycemic pro les and improved survival compared with those who did not use metformin.…”
Section: Metformin Treatment In Heart Failuresupporting
confidence: 91%
“…There was a trend of additional bene t in patients with LVEF ≤40%, but the difference was not statistically signi cant. This result is in line with another recent study, which showed that metformin was associated with improved outcomes in patients with HFrEF and diabetes [31]. Although the study population was small, this study also found that metformin-treated patients with HF had better glycemic pro les and improved survival compared with those who did not use metformin.…”
Section: Metformin Treatment In Heart Failuresupporting
confidence: 91%
“…Notably, when stratified by LV ejection fraction (LVEF), this relationship was strictly driven by risk reduction among patients with LVEF >40% [53]. On the other hand, a prospective cohort study by Benes et al [54] following 380 patients with diabetes and HF with reduced ejection fraction over an average of 3 years reported improved outcomes with metformin use. The authors found that diabetic patients on metformin demonstrated signs of more stable HF, including lower brain natriuretic peptide levels, lower mitral and tricuspid regurgitation severity, improved LV and right ventricular function, and usage of smaller doses of diuretics.…”
Section: Efficacy In Myocardial Injury and Hfmentioning
confidence: 99%
“…On subgroup analysis, the authors discovered improved outcomes regardless of HF severity or treatment. Furthermore, metformin treatment remained associated with improved outcomes even after adjustment for BMI, brain natriuretic peptide, and renal function, or after propensity score matching utilizing 81 pairs of patients [54].…”
Section: Clinical Studies: Latest Advancesmentioning
confidence: 99%
“…Of note, there was a non-significant 9% reduction in mortality in those with severe left ventricular dysfunction (HR, 0.91 (95% CI: 0.72-1.14)) [70]. A recent propensity score-matched observational study in 847 T2D patients with advanced HFrEF reported markedly lower B-type natriuretic peptide (BNP) levels, improved LVEF, and better event-free survival in metformin users than in controls irrespective of glycemic control [71]. However, these results should be interpreted cautiously, since metformin is often avoided in patients with multiple comorbidities, including HF and their comparators, such as sulfonylurea or SLT2 inhibitors, which may alter the estimated risk of HF.…”
Section: Metforminmentioning
confidence: 99%